Man up! Masculinity and (Homo)sexuality in René Depestre’s Transatlantic World - Jacqueline Couti; Jason C. Grant (Humanities, 2019)
The question of homosexuality in Francophone Caribbean literature is often overlooked. However, the ways in which the Haitian René Depestre’s Le mât de cocagne (The Festival of the Greasy Pole, 1979) and “Blues pour une tasse de thé vert” (“Blues for a Cup of Green Tea”), a short story from the collection Eros dans un train chinois (Eros on a Chinese Train, 1990) portray homoeroticism and homosexuality begs further study. In these texts, the study of the violence that surrounds the representation of sexuality reveals the sociopolitical implications of erotic and racial images in a French transatlantic world. Hence, the proposed essay “Man up!” interrogates a (Black) hegemonic masculinity inherited from colonialism and the homophobia it generates. This masculinity prescribes normative traits that frequently appear toxic as it thrives on hypersexuality and brute force. When these two traits become associated with violence and homoeroticism, however, they threaten this very masculinity. Initially, Depestre valorizes “solar eroticism,” a French Caribbean expression of a Black sexuality, free and joyful, and “geolibertinage,” its transnational and global expression. Namely, his novel and short story sing a hegemonic and polyamorous heterosexuality, respectively, in a postcolonial milieu (Haiti) and a diasporic space (Paris). The misadventures of his male characters suggest that eroticism in transatlantic spaces has more to do with Thanatos (death) than Eros (sex). Though Depestre formally explores the construction of the other and the mechanisms of racism and oppression in essays, he also tackles these themes in his fictional work. Applying Caribbean feminist and gendered lenses to his fiction bring to light the intricate bonds between racism, sexism and homophobia. Such a framework reveals the many facets of patriarchy and its mechanism of control.